Acute and Long-Term Treatment With Dapagliflozin and Association With Serum Soluble Urokinase Plasminogen Activator Receptor - Rotbain Curovic, Viktor; Houlind, Morten B.; Hansen, Tine W.; Eugen-Olsen, Jesper; Laursen, Jens Christian; Eickhoff, Mie K.; Persson, Frederik; Rossing, Peter (Frontiers in Pharmacology, 2022)
Background: Elevated soluble urokinase plasminogen activator receptor (suPAR) is highly associated with increased risk of diabetic complications. Dapagliflozin is a drug inhibiting the sodium-glucose co-transporter 2 (SGLT2i) in the kidney to decrease blood glucose, while also decreasing risk of kidney disease, heart failure, and death. Therefore, we have investigated suPAR as a monitor for treatment effect with dapagliflozin in diabetes. Methods: suPAR was measured in two double-blinded randomized clinical cross-over trials. The first trial investigated the effect of a single dose dapagliflozin 50 mg or placebo 12 hours after intake, in individuals with type 1 diabetes and albuminuria. The second trial investigated the effect of a daily dose dapagliflozin 10 mg or placebo for 12 weeks, in individuals with type 2 diabetes and albuminuria. suPAR was measured in serum samples taken, in the acute trial, after treatment with dapagliflozin and placebo, and in the long-term trial, before and after treatment with dapagliflozin and placebo. Effect of dapagliflozin on suPAR levels were assessed using paired t-test. Results: 15 participants completed the acute trial and 35 completed the long-term trial. Mean difference in suPAR between dapagliflozin and placebo in the acute trial after 12 hours was 0.70 ng/ml (95% CI: -0.66;1.33, p=0.49). In the long-term trial the mean difference was 0.06 ng/ml (95% CI -0.15;0.27, p=0.57). Conclusion: Based on our findings we conclude that suPAR is not a feasible marker to monitor the effect of treatment with dapagliflozin. Thus, a further search of suitable markers must continue. Clinical trials: NCT04193566, NCT02914691.